An Analysis of the Pronouncing of English Monophthongs by Kurdish EFL University Students (Northern Kurmanji Speakers) - Haji, Sabah S.; Mohammed, Fakhir O. (Humanities Journal of University of Zakho, 2019)
This study investigated the production of English monophthongs by Kurdish EFL learners at university level. Twenty native speakers of Northern Kurmanci (i.e. NK) undergraduate EFL learners read a list of sixty English words containing all the twelve English monophthongs. Their reading of the words was recorded and then transcribed by the researchers. The recording of each word was listened to several times for detecting mispronunciation of the monophthong vowel in it. After careful examination, results showed that the central vowels were the most problematic sounds for Kurdish EFL learners in terms of pronunciation followed by high back vowels. In principle, participants were expected to have problems with central vowels of English, mainly because they do not exist in their mother language, but the findings indicated that high back vowels also are quite noticeably difficult for them to correctly pronounce, even though these already exist in their mother language, NK Kurdish. The main reasons Kurdish EFL learners mispronounce English monophthong vowels are due to the absence of some of these vowels in their first language and also due to the participants’ lack of exposure to and practice of English pronunciation.